Nitrogen Doped γ‐Graphyne: A Novel Anode for High‐Capacity Rechargeable Alkali‐Ion Batteries. Issue 10 (13th February 2020) - Yang, Chaofan; Qiao, Chong; Chen, Yang; Zhao, Xueqi; Wu, Lulu; Li, Yong; Jia, Yu; Wang, Songyou; Cui, Xiaoli
Abstract: High energy density is the major demand for next‐generation rechargeable batteries, while the intrinsic low alkali metal adsorption of traditional carbon–based electrode remains the main challenge. Here, the mechanochemical route is proposed to prepare nitrogen doped γ‐graphyne (NGY) and its high capacity is demonstrated in lithium (LIBs)/sodium (SIBs) ion batteries. The sample delivers large reversible Li (1037 mAh g −1 ) and Na (570.4 mAh g −1 ) storage capacities at 100 mA g −1 and presents excellent rate capabilities (526 mAh g −1 for LIBs and 180.2 mAh g −1 for SIBs) at 5 A g −1 . The superior Li/Na storage mechanisms of NGY are revealed by its 2D morphology evolution, quantitative kinetics, and theoretical calculations. The effects on the diffusion barriers ( E b ) and adsorption energies ( E ad ) of Li/Na atoms in NGY are also studied and imine‐N is demonstrated to be the ideal doping format to enhance the Li/Na storage performance. Besides, the Li/Na adsorption routes in NGY are optimized according to the experimental and the first‐principles calculation results. This work provides a facile way to fabricate high capacity electrodes in LIBs/SIBs, which is also instructive for the design of other heteroatomic doped electrodes. Abstract : Nitrogen doped γ‐graphyne is synthesized through a facile and versatile mechanochemical and calcination method. The as‐prepared nitrogen doped γ‐graphyne presents excellent capacities both in Li (1037 mAh g −1 ) and Na (570.4 mAh g −1 ) ion batteries and superior rate capabilities of 526 mAh g −1 and 180.2 mAh g −1 at 5 A g −1, respectively. The superior Li/Na storage performance is demonstrated by experimental and first‐principles calculation results.